Corporate Governance Characteristics and Their Impact on Accounting Conservatism in SOEs Listed in the BUMN20 Index - Dhea Zafira Agustina; Ilham Ramadhan Ersyafdi; Muhammad Aras Prabowo; Siti khomsatun (Trescode Green Organization, 2026)
This study examines influence of corporate governance characteristics on accounting conservatism in State Owned Enterprises (SOEs) listed in the BUMN20 Index of Indonesia Stock Exchange during 2019–2023 period. The characteristics analyzed include audit committee, audit committee meetings, board of commissioners, independent commissioners, CEO retirement, and board of directors. Using a quantitative method with an associative approach, the study employs multiple linear regression to analyze data obtained from purposively selected SOEs within BUMN20 Index. The findings show that certain governance characteristics specifically board of commissioners and independent commissioners have a significant negative effect on accounting conservatism, while board of directors shows a significant positive influence. In contrast, audit committee, audit committee meetings, and CEO retirement exhibit no significant impact. These results emphasize the role of strong governance in improving financial reporting quality, particularly through application of conservative accounting practices to reduce risk of financial manipulation. However, the insignificance of audit committee variables suggests that their function in SOEs remains largely formalistic and not fully effective in overseeing accounting policies. Strengthening the competence, independence, and involvement of audit committees is therefore essential. Overall, this study contributes insights for academics, practitioners, and regulators in enhancing transparency, accountability, and public trust in SOEs.